Studium trvanlivosti betonů s popílky v prostředí XF - Brînduş-Simuţ, Jiřina (Vysoké učení technické v Brně. Fakulta stavební, 2014)
Práce je zaměřena na problematiku využití popílků ze spalování černého i hnědého uhlí v prostředí XF. Zabývá se vlivem létavého popílku na vlastnosti betonu a jejich experimentální ověření.

The work is focused on a problem of using ashes from burning black and brown coal in XF environment. It is oriented on influence of fly ash on properties of concrete and the experimental examining.
Study of durability of concrete with fly ash in an XF
Keywords: Trvanlivost betonů; prostředí XF; létavý popílek; Durability of concrete; XF environment; fly ash